2020
DOI: 10.1038/s41598-019-57094-3
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic and predictive potential of Ki-67 in triple-negative breast cancer

Abstract: As a cell proliferation biomarker, Ki-67 is principally used in ER+/HER2− breast cancer. However, the importance and the best cutoff point of Ki-67 in triple-negative breast cancer (TNBC) remains unclear and was evaluated in this study.A total of 1800 patients with early invasive TNBC between 2011 and 2016 at Fudan University Shanghai Cancer Center were consecutively recruited for this study. The optimal cutoff for Ki-67 was assessed by Cutoff Finder. Propensity score matching (PSM, ratio = 1:2) was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
92
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(104 citation statements)
references
References 30 publications
(29 reference statements)
10
92
0
2
Order By: Relevance
“… 28 Studies showed a high level of Ki-67 was associated with severity of tumor and poor prognosis in breast cancer and Ki-67 could be used to indicate different prognosis and treatment in TNBC patients. 29 …”
Section: Discussionmentioning
confidence: 99%
“… 28 Studies showed a high level of Ki-67 was associated with severity of tumor and poor prognosis in breast cancer and Ki-67 could be used to indicate different prognosis and treatment in TNBC patients. 29 …”
Section: Discussionmentioning
confidence: 99%
“…Our prognostic model determined 60% as the cut-off value for Ki67 status, which was much higher than those in other studies (e.g., 14% and 20%) [18,[21][22][23][24]. We reckoned that this situation was because of a lack of a standardised procedure for Ki67 assessment and the controversial Ki67 assay interpretation [25], and it was also because of determining the cut-off value for Ki67 by the ROC method, an univariate analysis method in previous study [19,23]. So the prognostic value of Ki67 index in breast cancer was to be further explored.…”
Section: Discussionmentioning
confidence: 60%
“…This proved that staining intensity of Ki-67 has not signi cant values in OS prediction of patients with BC. Zhu pointed that that setting the critical value of Ki-67 index as 30% is an independent prognosis factor of OS and DFS of three-yin cancer [19]. Patients with triple negative cancer and Ki-67 > 30% had relatively poorer prognosis, especially for patients in Stage I.…”
Section: Discussionmentioning
confidence: 99%